Thermal curved-fragments: A method for identifying anthropogenic fire in the archaeological record. (June 2019) - Cutts, Russell B.; Hlubik, Sarah; Campbell, Ross; Muschinski, Jana; Akuku, Pamela; Braun, David R.; Patterson, David B.; O'Brien, Joseph J.; Garrison, Ervan; Harris, J.W.K.
Abstract: The archaeology of fire is a developing field. One challenge centers on equifinality: distinguishing the affects of wildfire versus anthropogenic fire. Especially where evidence for control of fire by humans in the early Pleistocene remains debated, there is little consensus regarding what constitutes clear evidence of human-control . Another concern is preservation bias, which reduces clearly identifiable archaeological signatures of fire. In this paper we argue that a peculiar lithic angular fragment—termed thermal curved-fragment (TCF)—exhibits statistically distinct, quantitative evidence of the confluence of human-knapped stone tools and exposure to a high-energy, long-duration, ground-level fire (i.e., campfires). Experimental TCFs are described and compared to unfired knapping debitage, natural exfoliations and suspected archaeological TCFs. The provenance of these archaeological specimens has previously been argued to infer hominin-controlled fire at 1.5–1.6 Ma at the Koobi Fora Formation. We also present data from experiments exposing stone flakes (arranged as "scatters") of similar raw materials to those found in the Koobi Fora Formation to USDA prescribed burns in a variety of conditions approximating landscape fires. Results indicate that TCFs are formed specifically where (previously) knapped stone is exposed to high-energy ground level fires, similar to those seen in ethnographic campfires. Our analysis indicates that TCFs can be used in conjunction with other lines of evidence indicating the presence of anthropogenic fire in the archaeological record.